End-Stage Liver Disease Is a Strong Predictor of Early Mortality in Cryptococcosis. (15th December 2015) - Spec, Andrej; Raval, Krunal; Powderly, William G.
Abstract : End stage liver disease (ESLD) patients have a high mortality with cryptococcosis. In this retrospective cohort of 232 patients with cryptococcosis, 25 had ESLD. Their mortality was dramatically higher and more rapid, suggesting they are an important sub-population. Abstract: Background. Cryptococcosis in the setting of end-stage liver disease (ESLD) has been associated with high mortality. We sought to compare the outcome of cryptococcal disease in patients with ESLD to that of human immunodeficiency virus (HIV)-positive patients and to those patients without HIV or ESLD. Methods. We assembled a retrospective cohort of 232 consecutive cases of cryptococcosis in our institution, from 2002 to 2014, inclusively. We analyzed the cases for comorbidities, type of infection, and survival. Data were analyzed with t tests, Fishers Exact test, and Kaplan-Meyer analysis. Results. Twenty-five (10.8%) patients with cryptococcal infection had concomitant ESLD; of these, 5 (20%) presented with peritonitis. Most (17 of 25, 68%) did not have any other cause of immunocompromise that has been more classically associated with cryptococcosis. Patients with ESLD had a significantly higher mortality than HIV-positive patients and HIV-negative patients without ESLD (HIVNE) (80% vs 13.6% and 22.7%, respectively; P < .001). In addition, fatal outcome in ESLD patients occurred more rapidly than in HIVNE patients, with a median survival of 6 days (vs 17), despite a comparable time to diagnosis (6.2 vs 6.6 days). Conclusions. Cryptococcosis is an important morbidity in patients with ESLD. Patients with ESLD who are infected with Cryptococcus have a high and rapid mortality. This suggests that a high level of vigilance for cryptococcal infection should be kept in patients with ESLD.